Novel single-layer vanadium sulphide phases. (25th July 2018) - Arnold, Fabian; Stan, Raluca-Maria; Mahatha, Sanjoy K; Lund, H E; Curcio, Davide; Dendzik, Maciej; Bana, Harsh; Travaglia, Elisabetta; Bignardi, Luca; Lacovig, Paolo; Lizzit, Daniel; Li, Zheshen; et al.
Abstract: VS2 is a challenging material to prepare stoichiometrically in the bulk, and the single layer has not been successfully isolated before now. Here we report the first realization of single-layer VS2, which we have prepared epitaxially with high quality on Au(1 1 1) in the octahedral (1T) structure. We find that we can deplete the VS2 lattice of S by annealing in vacuum so as to create an entirely new 2D compound that has no bulk analogue. The transition is reversible upon annealing in an H2 S gas atmosphere. We report the structural properties of both the stoichiometric and S-depleted compounds on the basis of low-energy electron diffraction, x-ray photoelectron spectroscopy and diffraction, and scanning tunneling microscopy experiments.